EIF Venture Capital Survey 2024: Market sentiment - Antonia Botsari; Frank Lang (European Investment Fund (EIF), 2024)
The EIF VC Survey and the EIF Private Equity Mid-Market Survey (the largest combined regular survey exercises among General Partners on a pan-European level) provide an opportunity to retrieve unique market insights. This publication is based on the results of the 2024 VC Survey, conducted by the EIF with the support of Invest Europe. The paper focuses on the market sentiment. The study looks at the current situation, developments in the recent past and expectations for the future. It highlights substantial challenges, but also opportunities as perceived by survey participants. The main results are summarised and compared over time. The publication provides a valuable picture of the developments in the VC market in 2024 as well as an outlook for the near future.
Keywords: 330